Selective Preconcentration of Gold from Ore Samples - Hurmus Refiker; Melek Merdivan; Ruveyde Sezer Aygun (International Journal of Analytical Chemistry)
A simple and selective method has been developed for preconcentration of gold in ore samples. The method is based on use of N, N-diethyl-N’-benzoylthiourea (DEBT) as selective chelating agent and Amberlite XAD-16 as solid sorbent. Sorption behavior of gold with DEBT impregnated resin under optimized conditions has been studied in batch process. The gold ion capacity of the impregnated resin is calculated as 33.48 mg g−1 resin (0.17 mmol g−1 resin). The selective preconcentration of metal was examined using gold chelates prepared in column process under optimized conditions: pH, flow rate, volume of sample solution, nature of eluent, flow rate, and volume of eluent. Under optimum conditions, gold ions at the concentration of 0.015 μg mL−1 with a preconcentration factor of 6.7 have been determined by flame atomic absorption spectrometry (FAAS). The accuracy of the proposed method was validated by the analysis of a Cu-ore (semi-certified) supplied by CMC (Cyprus Mining Company, North Cyprus) and a certified reference material, Gold Ore (MA-1b Canmet-MMSL). Satisfactory results were obtained with a RSD of 7.6%. The highly selective proposed method does not require any interference elimination process.